Some welfare implications of who goes first? in WTO negotiations - Basudeb Guha-Khasnobis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
We envisage a logical framework to explain why some trade negotiations are delayed because parties differ on who should `go first'. In our model, there are substantive welfare implications depending on which party sets tariff rates (or subsidies) first in a strategic optimization exercise. When knowledge about cost levels are incomplete or missing, and hence must be guessed with a probability, the chances of conflict regarding who goes first are extremely high in the situation modeled in this paper. As an institution with some power to set the rules of negotiations, the WTO should be able to anticipate such conflicts in upcoming negotiations. It can then set the rule (in this case, dictate who should go first) depending on whose interest it wants to protect. There is a wide range of choices for the WTO in this regard: OECD consumer's surplus, OECD producers' loss, net exports of developing countries, firm profits, or even, world welfare as the sum of all these components.
Keywords: F10; F42; C72; 330; WTO; tariffs; subsidies; welfare; negotiation; Verhandlungstheorie; Handelsabkommen; WTO-Regeln